1988
DOI: 10.1128/jvi.62.6.2076-2082.1988
|View full text |Cite
|
Sign up to set email alerts
|

Cell lines containing varicella-zoster virus open reading frame 62 and expressing the "IE" 175 protein complement ICP4 mutants of herpes simplex virus type 1

Abstract: Vero cells were cotransfected with pSV2neo and a recombinant plasmid containing the varicella-zoster virus (VZV) open reading frame 62 (ORF62). Three neomycin-resistant cell lines were isolated and shown to complement two different ICP4 mutants (tsB21 and d120) of herpes simplex virus (HSV) type 1 (HSV-1). VZV-specific RNA could not be detected in these cell lines, but following infection with tsB21, a 4.3-kilobase VZV transcript was detected. This RNA increased in quantity when cells were infected in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 38 publications
2
42
1
Order By: Relevance
“…ICP4 is indispensable to the life cycle of the virus, is involved in negative regulation of IE genes, and is required throughout the viral replicative cycle for the expression of early and late genes (31). We previously showed that ORF62 protein is the functional homolog of HSV-1 ICP4 by demonstrating that ORF62-expressing cell lines can complement ICP4 mutants (15). This was confirmed when an HSV-1 recombinant which contains VZV ORF62 in place of the coding sequences for ICP4 was shown to grow in cell culture (11).…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…ICP4 is indispensable to the life cycle of the virus, is involved in negative regulation of IE genes, and is required throughout the viral replicative cycle for the expression of early and late genes (31). We previously showed that ORF62 protein is the functional homolog of HSV-1 ICP4 by demonstrating that ORF62-expressing cell lines can complement ICP4 mutants (15). This was confirmed when an HSV-1 recombinant which contains VZV ORF62 in place of the coding sequences for ICP4 was shown to grow in cell culture (11).…”
mentioning
confidence: 79%
“…African green monkey kidney cells (Vero; American Type Culture Collection, Rockville, Md.) were propagated as previously described (15) (20), were grown in Eagle's minimal essential medium supplemented with 10% heat-inactivated fetal bovine serum, 2 mM glutamine, penicillin G (100 U/ml), and streptomycin (100 pug/ml). FI-14 cells (VZV ORF62-expressing Vero cells [15]) and 3-3 cells (HSV-1 ICP27-expressing Vero cells [24]), provided by Priscilla A. Schaffer, were propagated as previously described.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA sequence analysis (Davison and Scott, 1986) and recent reports (Felser et al, 1988) have identified VZV genes that arc similar to HSV immediate early (IE) genes. VZV gene IE 62 encodes a protein of 175 Kd, which is the functional analog of HSV-1 ICP4, whereas VZV gene 63 displays sequence homology to HSV-I ICP22 (30 Kd).…”
Section: Introductionmentioning
confidence: 99%